Penerapan Model Pembelajaran Problem Based Learning pada Kompetensi Sistem Pengapian untuk Meningkatkan Hasil Belajar Siswa SMKN 1 Katapang - Airlangga Putra; Permana, Tatang; Mubarak, Ibnu (Pusat riset dan Inovasi Nasional, 2026)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model on student learning outcomes in the Ignition System competency at SMKN 1 Katapang. The background of this study stems from the low understanding of students regarding the ignition system material due to the dominant use of the Teacher-Centered Learning (TCL) model, which tends to make students passive and only memorize concepts without understanding the overall working process. PBL is considered more relevant because it emphasizes real problem-solving, critical thinking, collaboration, and analysis according to constructivist theory. The method used is a quasi-experiment with a Nonequivalent Control Group Design. The research subjects consist of two classes of 11th-grade Light Vehicle Engineering students: an experimental group using the PBL model and a control group using TCL, with a total population of 70 students. Data collection was done through pretests and posttests using a validated multiple-choice objective test instrument. Data analysis includes comparing the learning outcome improvements of both groups to determine the effectiveness of PBL. The results show a more significant improvement in learning outcomes in the class using the PBL model compared to the TCL class. This proves that the implementation of PBL is effective in improving analysis skills and diagnostic skills in the ignition system. Therefore, PBL is recommended as a more suitable teaching model for practice-based subjects in vocational schools, especially in automotive electrical competencies.